2023
DOI: 10.3389/fonc.2023.1115241
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair deficiency as circulating biomarker in prostate cancer

Abstract: Deleterious aberrations in DNA repair genes are actionable in approximately 25% of metastatic castration-resistant prostate cancers (mCRPC) patients. Homology recombination repair (HRR) is the DNA damage repair (DDR) mechanism most frequently altered in prostate cancer; of note BRCA2 is the most frequently altered DDR gene in this tumor. Poly ADP-ribose polymerase inhibitors showed antitumor activity with a improvement in overall survival in mCRPC carrying somatic and/or germline alterations of HHR. Germline m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 128 publications
0
10
0
Order By: Relevance
“…The use of liquid biopsy achieves 93% concordance between BRCA 1/2 mutations detected in tissue biopsy and those identified by ctDNA, 100% concordance for germline variants, and the detection of alterations in Tp53, RA, BRCA2/1, PI3K/AKT/mTOR, WNT/β-catenin pathway genes, RAS/RAF/MEK, and MSI-H is also possible [170]. In addition to their predictive value, ctDNA, PacBioScience, and Oxford Nanopore may have a predictive value for patients in active surveillance and salvage therapy; however, the cost and wide availability of genomic profiling tools continue to limit the development of this technology [171,172].…”
Section: Discussionmentioning
confidence: 99%
“…The use of liquid biopsy achieves 93% concordance between BRCA 1/2 mutations detected in tissue biopsy and those identified by ctDNA, 100% concordance for germline variants, and the detection of alterations in Tp53, RA, BRCA2/1, PI3K/AKT/mTOR, WNT/β-catenin pathway genes, RAS/RAF/MEK, and MSI-H is also possible [170]. In addition to their predictive value, ctDNA, PacBioScience, and Oxford Nanopore may have a predictive value for patients in active surveillance and salvage therapy; however, the cost and wide availability of genomic profiling tools continue to limit the development of this technology [171,172].…”
Section: Discussionmentioning
confidence: 99%
“…Authors have recently reported a breakthrough in PCa treatment that uses the DDR gene mutation to target the tumor only while protecting healthy cells with intact DDR pathways. This discovery has led to numerous clinical trials that take advantage of these defects, and numerous PARP inhibitors, such as olaparib, rucaparib, niraparib, talazoparib, and veliparib, have been successfully tested in patients with a variety of DDR gene mutations, including BRCA1 , BRCA2 , ATR , ATM , CHEK1/2 , and PALB2 ( Catalano et al, 2023 ).…”
Section: Clinical and Therapeutic Implications Of Dna Damage Response...mentioning
confidence: 99%
“…In recent years, the PCa treatment PARPi—poly (ADP-ribose) polymerase inhibitors—has been approved by the FDA ( Catalano et al, 2023 ). Patients with mutations in the DDR response genes BRCA2, ATM , and BRCA1 reported significantly greater response rates to olaparib than noncarriers in one of the earliest trials of PARPi in patients with advanced PCa ( Gurley and Kemp, 2001 ).…”
Section: Clinical and Therapeutic Implications Of Dna Damage Response...mentioning
confidence: 99%
“…However, robust evidence is still lacking to support the clinical utility of circulating cytokines and other soluble proteins measurements to predict immunotherapy response in the real world. 6 This uncertain scenario may not only reflect the complex biology of an inflammation signaling cascade, but also could be due—at least in part—to the unattained standardization of assay methods and inaccurate choice or preparation of biological samples.…”
Section: Introductionmentioning
confidence: 99%